Role of transabdominal ultrasound in evaluating patients with acute urinary retention (AUR) due to benign prostatic hyperplasia (BPH) - Gupta, S D; Hossain, T M S; Rahman, M M; Hooda, M N; Kashem, M A; Jahan, I; Bhuiyan, A K M Z I (Bangladesh Journal of Urology, 2012)
Acute retention of urine (ARU) is one of the most serious complication of benign prostatic hyperplasia(BPH). However there is no consensus on the management of ARU due to BPH. In this study we prospectively evaluated 58 patients with acute urinary retention in different hospitals in Dhaka city due to BPH by a simple noninvasive method based on intravesical prostatic protrusion (IPP) using transabdominal ultrasound. Catheterization with an indwelling catheter was done at hospital admission. History taking and physical examinations were done in all cases. Transabdominal ultrasound was done to assess the prostatic volume and intravesical prostatic protrusion (IPP).IPP were divided into three grades. The voiding trial was judged to be unsuccessful if the patient failed to reestablish satisfactory micturition. After catheter removal in this study 34 patients failed to void well. There were more patients with higher grade IPP in the group with failure than in the group with a successful trial off catheter. These patients were followed up for one year, This study reveals that the greater the protrusion, the more severe the obstruction, Grade 3 IPP patients are more likely to have recurrent urinary retention. The degree of IPP influences the outcome. BJU 2010; 13(2): 57-59